Modeling the atomic-scale structure, stability, and morphological transformations in the tetragonal phase of LaVO4 - Gouveia, Amanda F.; Ferrer, Mateus M. [UNESP]; Sambrano, Júlio R. [UNESP]; Andrés, Juan; Longo, Elson (Elsevier, 2016)
In this communication, a systematic study of the surface structure, including energy management during morphological transformations of tetragonal phase of LaVO4, has been carried out. For this study, we combined experimental findings and first-principles calculations to develop a Wulff construction model. Our findings can help further understand the synthetic control of crystal shape via tuning of surface chemistry.
Keywords: Morphology; Surface energy; t-LaVO4; Wulff construction